2020
DOI: 10.31695/ijasre.2020.33799
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance between Bi-facial and Mono-facial 10kW Photovoltaic Power Systems

Abstract: This paper is based and written on performance analysis of a 10kW Grid-connected solar power system with a comparison in integration of bifacial photovoltaic systems vs mono-facial photovoltaic systems. Thus, all these tastings were carried out on computer simulations using PVSyst6 software & MATLAB/Simulink. These simulations were done considering different albedos and tilt angles in order to identify power variations under different environmental conditions. The selected panels used monocrystalline type-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The growth that bifacial technology has had in recent years and the little knowledge we have about its performance has led to different studies being carried out in the world to understand how parameters such as albedo, inclination, height, and separation between sheds (pitch) affect its energy performance. The results of these studies [14][15][16][17][18][19] have shown that bifacial technology can obtain up to 30% more energy compared to monofacial technology. However, in tropical sites bifacial technology has not been well studied and it is unknown under which parameters bifacial technology can perform better, therefore, this research focuses on evaluating and comparing the energy performance of bifacial technology with respect to monofacial technology according to 4 main parameters of affectation: 1) inclination, 2) pitch, 3) albedo and 4) height from the ground, in a tropical location.…”
Section: Introductionmentioning
confidence: 99%
“…The growth that bifacial technology has had in recent years and the little knowledge we have about its performance has led to different studies being carried out in the world to understand how parameters such as albedo, inclination, height, and separation between sheds (pitch) affect its energy performance. The results of these studies [14][15][16][17][18][19] have shown that bifacial technology can obtain up to 30% more energy compared to monofacial technology. However, in tropical sites bifacial technology has not been well studied and it is unknown under which parameters bifacial technology can perform better, therefore, this research focuses on evaluating and comparing the energy performance of bifacial technology with respect to monofacial technology according to 4 main parameters of affectation: 1) inclination, 2) pitch, 3) albedo and 4) height from the ground, in a tropical location.…”
Section: Introductionmentioning
confidence: 99%